Land subsidence/rebound change after Hazelwood mine rehabilitation - Waghorne, EP; Disfani, MM (Mine Closure 2019: 13th International Conference on Mine Closure, 2019)
As the power stations in the Latrobe Valley, Victoria, reach the end of their economic life, mine closures are anticipated. The closure of ENGIE’s Hazelwood Power Station and associated mine has already occurred and mine rehabilitation and closure planning are well under way. During mining, pumping from deep, high pressure aquifers was required to reduce mine stability risks. This pumping, combined with water extraction (by others) for domestic supply and agricultural use, has lowered aquifer water pressures across the region. As a result, there has been gradual land subsidence of 0.3 to 0.5 m across the region, with 1 to 2 m close to the mines. The Hazelwood mine rehabilitation plan includes the construction of an internal lake to balance uplift forces from the aquifers, allowing aquifer pumping at the mine to cease. Over the following decades, the aquifer pressure will recover, and a reduction of in situ effective stresses will occur so that compressible sediments in the strata will swell. Whilst future changes to the land surface are expected to occur slowly it will be important to understand the magnitude of the change and to assess any impacts on community infrastructure. As there had been limited investigations into the swell properties of the sediments in the Latrobe Valley, an investigation was commenced at the University of Melbourne on the thick compressible coal seams and clay sediments found near the mine. The effect during loading, of creep and chemical/micro-structure changes on the swell properties of brown coal was also studied. A background of aquifer pressure changes and subsidence in the Latrobe Valley over the last 60 years is provided, with recent test results and discussion of their significance on land subsidence and rebound prediction over the next 50 to 100 years.
Keywords: mine rehabilitation; mine closure; subsidence; rebound; aquifer; strata testing.